Sentiment dynamics and stock returns: the case of the German stock market - Thomas Lux (Kiel Institute for the World Economy (IfW), 2008)
We use weekly survey data on short-term and medium-term sentiment of German investors in order to study the causal relationship between investors' mood and subsequent stock price changes. In contrast to extant literature for other countries, a tri-variate vector autoregression for short-run sentiment, medium-run sentiment and stock index returns allows to reject exogeneity of returns. Depending on the chosen VAR specification, returns are found to either follow a feedback process caused by medium-run sentiment, or returns form a simultaneous systems together with the two sentiment measures. An out-of-sample forecasting experiment on the base of estimated VAR models shows significant exploitable linear structure for the richer VAR(5) model. Out-of-sample trading experiments underscore the potential for excess profits from a VAR-based strategy compared to the buy-and-hold benchmark.
Keywords: G12; G14; C22; 330; Investor sentiment; opinion dynamics; return predictability; Kapitalertrag; Börsenkurs; Anlageverhalten; Meinung; Wertpapieranalyse; Prognoseverfahren; Schätzung; Deutschland